1993
DOI: 10.1038/362603a0
|View full text |Cite
|
Sign up to set email alerts
|

A structural motif in the variant surface glycoproteins of Trypanosoma brucei

Abstract: The variable domain of the trypanosome variant surface glycoprotein (VSG) ILTat 1.24 has been shown by X-ray crystallography to resemble closely the structures of VSG MITat 1.2, despite their low sequence similarity. Specific structural features of these VSGs, including substitution of carbohydrate for an alpha-helix, can be found in other VSG sequences. Thus antigenic variation in trypanosomes is accomplished by sequence variation, not gross structural alteration; the extensive sequence differences among VSGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(139 citation statements)
references
References 47 publications
4
134
0
Order By: Relevance
“…Structural studies of the trypanosome VSGs led to the conclusion that “the African trypanosomal antigens accomplish antigenic variation through the variation of sequence and limited conformational modification and not by gross alteration of structure.”11 More recent studies have shown further diversification of this basic fold to allow the development of ligand binding in proteins that bind nutrients or innate immune factors. Furthermore, a more simple monomeric, and probably ancestral, three‐helical bundle architecture is found in receptors such as that for haptoglobin‐haemoglobin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural studies of the trypanosome VSGs led to the conclusion that “the African trypanosomal antigens accomplish antigenic variation through the variation of sequence and limited conformational modification and not by gross alteration of structure.”11 More recent studies have shown further diversification of this basic fold to allow the development of ligand binding in proteins that bind nutrients or innate immune factors. Furthermore, a more simple monomeric, and probably ancestral, three‐helical bundle architecture is found in receptors such as that for haptoglobin‐haemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies, conducted some 20 years ago, demonstrated that, despite a high degree of sequence diversification, VSGs share a common fold 11. More recent studies have shown that this fold, and the related three‐helical bundle architecture, can diversify further, generating ligand‐binding functions essential for trypanosome survival and human infectivity 12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To survive long-term, T. brucei must generate novel VSG sequences through recombination; mechanisms may include domain shuffling (7) and gene conversion among silent, subtelomeric gene copies or possibly in situ within the expression site (8). Functional variant antigens in T. brucei consist of a-and b-type VSG (hereafter a-VSG and b-VSG), which share the cysteine-rich C-terminal domain (CTD) but are otherwise distantly related (9)(10)(11). Although VSG are known to occur in T. congolense and T. vivax (12)(13)(14)(15)(16), the repertoire of variant antigens in these species is uncharacterized.…”
mentioning
confidence: 99%
“…Based on earlier partial amino acid sequence analyses of the VSG proteins from LouTat 1 and 1A (Inverso et al, 1988), we predict that the precursor molecule is processed to a mature VSG of 461 amino acids, beginning at the N-terminus with threonine 27 and ending with conserved residues common to type I VSG molecules at the C-terminus. The LouTat 1=1A VSG molecule also contains conserved residues throughout the molecule, which are common to VSGs as a family (Rice-Ficht et al, 1981;Reinitz et al, 1992;Blum et al, 1993).…”
Section: Resultsmentioning
confidence: 99%